Bioartificial Liver Support - Vincent G Bain; Jose Luis Montero; Manuel de la Mata (Canadian Journal of Gastroenterology)
Bioartificial liver support has been increasingly the focus of both basic and clinical research in an attempt to replicate the multiplicity of normal liver function. The concept is attractive because, if it is effective, patients with acute liver failure may be supported until native liver regeneration occurs or, by optimizing their condition, until liver transplantation is possible. Current bioartificial liver support systems utilize primary porcine hepatocytes or transformed human hepatocytes, which are housed within a bioreactor, through which the patient's blood or plasma is pumped in an extracorporeal circuit. The optimal source for the hepatocytes is an area of debate; however, a genetically engineered cell line may provide optimal function. Novel three-dimensional matrices that anchor the hepatocytes are being designed to mimic architectural features of the normal liver. Large multicentre, randomized, controlled trials are ongoing following several pilot studies. Serious side effects such as hemodynamic instability and immune reactions have been infrequent. Much controversy, however, surrounds the issue of possible transmission of pig endogenous retrovirus to humans, and current trials are being carefully monitored. Bioartificial liver support is a promising technology, and the results of current and planned studies are awaited with great interest.